Efecto de la intervención educativa en el conocimiento y prácticas preventivas sobre malaria en pobladores de Santo Tomás Iquitos 2021 - Lozano Gómez, Christian Jack (2024)
The objective of the study was to determine the effect of the educational intervention on the knowledge and practice of preventive measures against Malaria in residents aged 18 to 65 years of Santo Tomás, Iquitos 2021. The method was quantitative with a quasi-experimental design, it included 30 people, The techniques were the interview, home visit, educational and demonstration session, the instruments were the Malaria knowledge questionnaire, checklist and educational intervention program. The results were: of 30 (100.0%) people, in terms of knowledge about Malaria, before the educational intervention, 25 (83.3%) had poor knowledge and 5 (16.7%) had good knowledge; while after the intervention 28 (93.3%) had good knowledge and 2 (6.7%) had poor knowledge. Regarding the practice of preventive measures against Malaria, before the intervention 28 (93.3%) carried out inadequate practices and 2 (6.7%) carried out appropriate practices; while after the intervention 19 (63.3%) carried out appropriate practices and 11 (36.7%) carried out inappropriate practices. To determine the effect of the educational intervention, the Wilcoxon rank statistic was applied, obtaining a value of p = 0.000 in knowledge about Malaria, and when determining the effect of the educational intervention in the practice of preventive measures on Malaria, p = 0.000 was obtained. The work concludes that the educational intervention was effective in knowledge about Malaria and in the practice of preventive measures against Malaria.